Psychological Capital as Strategic Capital to Improve Job Performance - Hariani, Mila; Putra, Arif Rachman (Metromedia, 2024)
Psychological Capital (PsyCap) has become a key concept in human resource management that focuses on its influence on individual job performance. This study uses a literature review approach to analyze the relationship between PsyCap and job performance. The results show that PsyCap, which consists of four dimensions, namely hope, self-efficacy, resilience, and optimism, contributes significantly to improving job performance. The hope dimension provides motivation to design clear goals, self-efficacy increases confidence to complete tasks, resilience helps individuals bounce back from failure, and optimism encourages a positive view of the expected results. The study also revealed that the implementation of PsyCap in the workplace still faces challenges, especially in terms of developing structured training programs and cultural context relevance. However, with strong management support and a positive organizational culture, PsyCap can be leveraged as strategic capital to improve individual productivity and organizational competitiveness. This research concludes that PsyCap is a valuable psychological capital for individuals, and as a tool that can be optimized to support organizational success in the modern era.